Perbaikan Pembelajaran Mata Kuliah Listrik Dan Magnet Melalui Pemberian Tugas Presentasi Aplikasi Elektrostatik Dalam Teknologi - Zulirfan Zulirfan; Yennita Yennita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2010)
This action research is aimed to improve learning outcomes of electricity and magnetism subject throughincreased activity of students in preparing for and carrying out presentations on technologies that apply theconcept of electrostatic. Presentation topic is selected in the application of the concept of electrostatic in thetechnology products and natural phenomena that is familiar to students. Subjects were 59 students of PhysicsEducation of Faculty of Education Riau University at semester 6 academic year 2008/2009. This researchuses Kemmis Model with three cycles. Based on the data analysis, it can be concluded that the quality of thepresentation slides are prepared by students which increases each cycle until it reaches reaching the highcategory in cycle-3. Activity of presentation also increased of each cycle despite only reaching into thecategory of middle on a cycle-3. Student learning outcomes are categorized as high. When compared with thelearning outcomes of the previous year, the result of this learning strategy has increased. Meanwhile,students' motivation has increased between before and after learning.